2003
DOI: 10.1046/j.1365-2923.2003.01407.x
|View full text |Cite
|
Sign up to set email alerts
|

Learning from lives: a model for health and social care education in the wider community context

Abstract: We have successfully developed a partnership model of community-based education and shown that it leads to significant changes in attitude in students and enables them to learn in an active, patient-focused way about the complexities of delivery of care outside the secondary care environment. We have identified the key requirements for implementation of the model in other centres.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2004
2004
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 9 publications
1
23
0
Order By: Relevance
“…In particular, although practice at sites located within the community can still deliver good educational outcomes (Anderson et al 2003), we showed that bringing students into the homes of patients themselves can produce a better educational experience. We hope that our success in adapting this concept to an underserved Asian community can serve as the catalyst for greater adoption of this idea and concurrently address health disparities in Asian societies.…”
Section: Discussionmentioning
confidence: 80%
“…In particular, although practice at sites located within the community can still deliver good educational outcomes (Anderson et al 2003), we showed that bringing students into the homes of patients themselves can produce a better educational experience. We hope that our success in adapting this concept to an underserved Asian community can serve as the catalyst for greater adoption of this idea and concurrently address health disparities in Asian societies.…”
Section: Discussionmentioning
confidence: 80%
“…The design of individual learning events was influenced by educational theories relating to the process of learning as adhered to by cognitive constructivists such as Piaget (1973) extolling a staged process of knowledge construction. Additionally, the process of social learning was considered, with learning communities in practice supporting medical curriculum primed for later IPE arrangements (Wenger, 1998;Anderson, et al 2003). Social constructivist theorists such as Bandura (1977) who place emphasis on constructing meaning through learning with others in a social context were utilised.…”
Section: Our Interprofessional Curriculummentioning
confidence: 99%
“…In addition, community partnerships with paediatric residency training programmes have demonstrated opportunities for shared learning between paediatric residents and community staff (Meyer et al, 2005). Ensuring adequate levels of resourcing for community education programmes and embedding them within mainstream curricula are consistently identified as critical to their success (Kuo & Slavin, 2001;Anderson et al, 2003). In the Adelaide programme community agency resource constraints posed the greatest threat to the continued success of the programme.…”
Section: Community Child Health For Medical Studentsmentioning
confidence: 99%
“…Three programmes that were developed around multi-agency, primarily non-medical, patient-centred community experiences for medical students were identified following review of 705 citations (Lennox & Petersen, 1998;Juster & Edwards, 2001;Young et al, 2002;Anderson et al, 2003). One programme had two associated publications, which provided some longitudinal information (Lennox & Petersen, 1998;Anderson et al, 2003), and one had a specific focus on child health ( Juster & Edwards, 2001). The logistical challenges associated with delivering community programmes and the substantial resource implications were acknowledged (Lennox & Petersen, 1998;Anderson et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation